Modelling permeability behaviour of polymer nanocomposites - Lu, Chungsheng; Mai, Y. (Woodhead Publishing Ltd, 2010)
In this chapter, we briefly review recent advances in modelling permeability behaviour of nanoplatelet-reinforced polymer nanocomposites, with a special focus on tortuosity-based models, aspect ratio-controlled percolation, and estimations of critical volume fractions and exponents. Also discussed is the influence of large-scale morphology and disorder of nano-additives in polymer nanocomposites on their physical properties.